Pricing and Adaptation Strategies in Market Dynamics: A Systematic Literature Review - Hasanah, Ulfah Yuziya; Rino, Rino (Electronic Journal of Education, Social Economics and Technology, 2025)
This systematic literature review aims to explore pricing strategies and adaptation in the context of modern marketing management, considering the impact of digital technologies and data analytics. Using the PRISMA methodology, this review identifies approaches, models, and key factors that influence the success of pricing strategies. The results highlight the importance of a value-based pricing approach, considering market dynamics and customer behavior, as well as the opportunities and challenges associated with implementing the latest technologies. This review provides practical insights for managers in designing and implementing effective pricing strategies in the digital era, emphasizing the need for a holistic approach, capability development, and cross-functional collaboration. By integrating insights from multiple research streams, this review offers a comprehensive perspective on the determinants of success of pricing strategies in a changing business landscape.